Holocord Syrinx, Tethered Cord and Diastematomyelia: Case Report and Review of Literature - Maheshwari, A; Yadav, D; Aneja, S; Kaur, S; Patra, B; Seth, A (Journal of Nepal Paediatric Society, 2012)
Syringomyelia refers to the presence of cavities within the spinal cord or a dilatation of the central spinal cord canal. In 90% of cases, syringomyelia is associated with a Chiari I malformation. The association of syringomyelia with tethered cord is well known but syrinxes associated with these defects are usually below vertebral level T6. Holocord syrinx associated with tethered cord is rare and is almost always associated with Chiari 1 malformation. To the best of our knowledge, only a single case report of holocord syrinx with tethered cord has been reported, but this patient had multiple overt lumbosacral defects (tethered cord, meningocele and diastematomyelia). We are reporting a three year old child with holocord syrinx with tethered cord and diastematomyelia and no evidence of Chiari malformation, meningocele or any overt spinal malformation and minimal neurological abnormalities. J Nepal Paediatr Soc 2012;32(2):169-171 doi: http://dx.doi.org/10.3126/jnps.v32i2.6098